KAJIAN MUTU BUBUR INSTAN BERAS MERAH YANG DIFORTIFIKASI KONSENTRAT PROTEIN IKAN PATIN (Pangasius hypopthalmus) - Hutahaean, Benget; Syahrul, Syahrul; Dewita, Dewita (Fakultas Perikanan dan Kelautan Universitas Riau, 2013)
The objective of this study was to evaluate the quality changes of instan brownrice porridge fortified with catfish protein concentrate during storage. Instant brownrice proridge was prepared from glutinous red rice flours (33%), skim milk (50%);corn oil (2%); sugar (5%) and forfified with 10% catfish protein concentrate. Theproduct was stored at room temperature for 45 days. Sensory analyses, peroxide,totalbacterial count, Escherichia coli, Staphylococcus aureus, and mold were made every0, 15, 30 and 45 days. The result indicated that the quality of porridge decresed duringstorage. The sensory value, peroxide, total bacterial count, Escherichia coli, Staphylo-coccus aureus and mold of the porridge at initial to the end of storage was 3, 59 - 3,30; 0 - 9,6 meq/1000g; 2, 0 x 103 - 1, 0 x 104 Cfu/g; 0, 2 x 102 - 1,0 x 102; 0, 15 x 102 –1,0 x 102 koloni/g. The was no mold growth identified during storage.